Bibliometric Analysis of Research Trends in Court Case File Preservation within the Scopus Database from 2018-2023 - Yunianti, Anisa Dwi; Salim, Tamara Adriani (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This study aims to conduct a bibliometric analysis of the trends in scholarly publications on the preservation of court case-files over the past five years, from 2018 to 2023. The research seeks to identify the current trends in existing studies and to determine the types of research that are lacking or require further exploration regarding the preservation of court case-files for their potential contributions to legal oversight, historical record-keeping, and accountability within the legal system in the future. Relevant data was collected by extracting information from the Scopus database, with inclusion criteria focusing on English-language social science subjects, followed by analysis using the VOSviewer application. The analysis of the trend in research on the preservation of court case-files revealed 72 (seventy two) documents related to this topic. The data analysis mapping using VOSviewer resulted in 8 (eight) major clusters that became the focus of the research, with key terms including digital storage, preservation, digital preservation, electronic document identification, law, records management, and archives management. This research highlights the significance of preserving court case files in upholding legal fairness and transparency. An improved comprehension of preservation methods can bolster the integrity of the judicial process and guarantee the accurate maintenance of historical records for future use, thereby fostering accountability and trust within the legal system. The results of this study are intended to inform practitioners, policymakers, and researchers about important deficiencies in the current literature, while also encouraging more extensive inquiries into this essential subject.